Bio-materials for intramedullary pin application in canine femur: a comparative analysis - Minhaz Husain; Rupinder Singh; Bahadur Singh Pabla; Gurwinder Singh; J. P. Davim (Exploration of BioMat-X)
Aim: In this study, the finite elements analysis (FEA) was performed on an intramedullary (IM) pin to be used in the canine femur. The 03 different biomaterials [17-4-precipitated hardened (PH)-stainless steel (SS), nickel alloys (Ni)-625, titanium alloys (Ti)-6Al-4V] were selected for comparative FEA. In-vitro analysis was also performed in simulated body fluid (SBF) on selected biomaterials for possible application in the canine femur. Methods: FEA was performed on 03 different biomaterials (17-4-PH-SS, Ni-625, and Ti-6Al-4V) based on Von-Mises criteria (at an applied load of 1,500 N, cell type: tetrahedron, grit size: 0.15 mm, number of nodes: 213,989 and elements: 145,012). The distal end of the IM pin was fixed, and the load was applied to the proximal end. In-vitro analysis was performed (on a potentiostat setup) to establish the corrosion rate of various biomaterials (17-4-PH-SS, Ni-625, and Ti-6Al-4V). Results: The results of FEA show Ni-625 absorbed the maximum Von-Mises stress in the case of tensile and compression loading (104.12 MPa). In the case of torsion loading, the maximum Von-Mises stress was absorbed by 17-4-PH-SS (63.331 MPa). The maximum Von-Mises elastic strain (0.00093473) was observed for Ti-6Al-4V while tensile and compression and minimum deformation (0.013869 mm) in tensile loading. Conclusions: Based on this study, the maximum safety factor against failure (N) [ratio of 0.2% of yield strength (σy) to the Von-Mises stress (σv)] was observed as 10.75, 11.38, and 15.89, respectively, for tensile, compression, and torsional loading in the case of Ti-6Al-4V. Also, the better biocompatible material for the orthopaedic implant application based on the corrosion result is Ti-6Al-4V due to a lower corrosion rate (2.63211 × 10–10 mm/year) in comparison to 17-4-PH-SS and Ni-625. Overall, the Ti-6Al-4V is a better material than 17-4-PH-SS and Ni-625 for the intended application.